The Educational Values of Numbak Sampi Tradition at Banjar Delod Uma, Kaba-Kaba - Karmini, Ni Wayan (Opción, 2019)
This paper discusses the reasons, the implementation process of the tradition of Numbak Sambi, and the educational values via qualitative research method. As a result, after going around the Banjar Delod Uma area and the sampi, the traditional process of numbak sampi was continued by slaughtering sampi, and processing it into Caru and food as a wish to get a pice. In conclusion, the tradition of numbak sampi has educational values such as the value of tattwa, which is the belief in the existence of Ida Sang Hyang Widhi Wasa and Bhuta Kala.